Wokół „Wyprawy Wołodyjowskiego na kresy” - Uliasz, Stanisław (Wydawnictwo Uniwersytetu Rzeszowskiego, 2017)
The author’s attention is focused on the analysis of Zdzisław Grodecki’s novel entitled “Wyprawa Wołodyjowskiego na kresy” (“Wołodyjowski’s expedition to the Eastern Borderlands”) published in 1929 in Lviv. The novel is set in the context of various discourses, among which the discourse on the Eastern Borderlines appears to be the most significant one, as it regards interwar Polish Eastern Territories as a strongold preserving the Polish identity. Crucial to Grodecki’s work are references to a cult classic “The Trilogy” by Henryk Sienkiewicz, including the notion of characters on “loan” which is enhanced by a strategy which might be described as a follow-up. The author of the paper analyzes the presence of literary symbols within national community, stereotyping, as well as coaxing strategies.
On Grodecki’s „Wyprawa Wołodyjowskiego na kresy” (“Wołodyjowski’s expedition to the Eastern Borderlands”)
Keywords: Interwar Polish Eastern Territories; Eastern Borderlines discourse; references to “The Trilogy” by Henryk Sienkiewicz; stereotyping; depiction of the Eastern Borderlines and its ideologization; Kresy Wschodnie Polski międzywojennej; dyskurs kresowy; nawiązania do Trylogii H. Sienkiewicza; stereotypizacja oraz ideologizacja obrazu pogranicza